Massacre, trial and ‘choral memory’ in Sant’Anna di Stazzema, Italy (1944-2005) - Di Pasquale, Caterina (International journal of transitional justice, 2012)
In 2003, a trial of 10 Nazi officers accused of perpetrating a massacre in Sant’Anna di Stazzema began in Italy. The trial took place almost 60 years after the massacre, in which approximately 400 civilians, mainly women, children and elderly people, were killed. This article, based on eight years of ethnographic research, analyses these 60 years by concentrating on how the survivors and the relatives of the victims were able to overcome the trauma and accept, at the end, a late reconciliation. The article contends that ‘choral memory’ acted as a strong resistance mechanism, protecting the village community from the destructive power of violence, as well as from later public oblivion, and making possible its material survival and symbolic continuity.